Virus recognition with terahertz radiation: drawbacks and potentialities. (18th May 2021) - Di Fabrizio, Marta; Lupi, Stefano; D'Arco, Annalisa
Abstract: Virus sensing is earning great interest for recognition of dangerous and widely spread diseases, such as influenza A (virus subtypes H1N1, H3N2 etc), severe acute respiratory syndrome, Middle East respiratory syndrome etc. Many molecular and biological techniques have been developed and adopted for virus detection purposes. These techniques show some drawbacks concerning long collection time and data analysis, sensitivity, safety, costs etc. Therefore, new sensing approaches have been proposed for overcoming these limitations. In this short-review, we explore the emerging and challenging terahertz radiation technology and its applications to virus high-sensitivity remote-sensing devices.